Peruvian ushuñari coffee: sensory profile, cherries preference and captive management of Nasua nasua - Loza-Del Carpio, Alfredo; Velásquez-Monge, Cinthya Nataly; Valencia-Mamani, Juan José; Valencia-Mamani, Juan Carlos (Ecosistemas y Recursos Agropecuarios, 2023)
Trends in demand for specialty coffees and new quality options are gradually increasing, hence an alternative is post-harvest bioprocessing of cherry with wild animals. Therefore, the objective was to evaluate the sensory profile of coffee digestively processed by the ushuñari (Nasua nasua L.) and determine their preference for cherry according to varieties. Three ushuñaris were fed with coffee cherries of Caturra, Típica, Catimor and Bourbón varieties, undigested grains were collected from their feces and processed using SCAA (Specialty Coffee Association of America) protocol to determine their quality in cup, compared with a control without ushuñari, analyzing the data under a 2*4 factorial ANOVA (two types of coffee and four varieties). To determine their preference for varieties, combined cherries were offered in known weight and by difference of what was eaten, the preferred varieties will be defined, applying relative importance indices and ANOVA. The sensory profile showed significantly superior characteristics in the ushuñari coffee compared to the control in most sensory attributes (p < 0.05), with scores of 84.77 and 82.62 respectively, in addition, 100% of the ushuñari coffee samples were categorized s special and all varieties surpassed Caturra. Animals preferred Típica and Caturra cherries, although this did not affect its organoleptic quality. Bioprocessing of the four varieties of coffee significantly improved their organoleptic qualities, making them a special product alternative, considering a sustainable management of ushuñari in captivity.